2022
DOI: 10.1039/d2cc05377b
|View full text |Cite
|
Sign up to set email alerts
|

Stability challenges of carbon-supported Pt-nanoalloys as fuel cell oxygen reduction reaction electrocatalysts

Abstract: Carbon-supported Pt-based nanoalloys (CSPtNs) as the oxygen reduction reaction (ORR) electrocatalysts are considered state-of-the-art electrocatalysts for use in proton exchange membrane fuel cells (PEMFCs). Although their ORR activity performance is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 196 publications
4
41
0
Order By: Relevance
“…Recently, transition-metal phosphides-based carbon (TMPs/C) composites, such as the nanohybrid of TMP nanoparticles (NPs) distributed on a C support, have emerged rapidly as a promising alternative to expensive noble-metal-based electrocatalysts, exhibiting significant bifunctional activity for both OER and ORR in ZABs and a distinct economical advantage. , In this case, the phosphorus and metal sites in TMPs not only act as active sites (e.g., proton acceptor and oxygenated intermediate acceptor) during the electrocatalytic process but also facilitate charge transfer due to the higher electrical conductivity of phosphides than their oxide counterparts. , The nanocomposites composed of TMP NPs and a heteroatom-doped C support demonstrated excellent electrocatalytic performance and good stability in a tough medium with a wide pH range, attributed to their polytropic composition/structures. Nonetheless, the synthesis of performance TMPs/C composites still suffers from the coalescence and subsequent poor dispersion of NPs during pyrolysis, which can severely reduce the site density as well as activity of the as-prepared electrocatalysts. , Moreover, the naked TMPs dispersing on the C matrix are subject to poor durability under harsh electrochemical conditions, , for example, acidic/alkaline media at high voltages. Therefore, the development of a TMPs/C electrocatalyst with both high activity and durability for ZABs is of critical importance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transition-metal phosphides-based carbon (TMPs/C) composites, such as the nanohybrid of TMP nanoparticles (NPs) distributed on a C support, have emerged rapidly as a promising alternative to expensive noble-metal-based electrocatalysts, exhibiting significant bifunctional activity for both OER and ORR in ZABs and a distinct economical advantage. , In this case, the phosphorus and metal sites in TMPs not only act as active sites (e.g., proton acceptor and oxygenated intermediate acceptor) during the electrocatalytic process but also facilitate charge transfer due to the higher electrical conductivity of phosphides than their oxide counterparts. , The nanocomposites composed of TMP NPs and a heteroatom-doped C support demonstrated excellent electrocatalytic performance and good stability in a tough medium with a wide pH range, attributed to their polytropic composition/structures. Nonetheless, the synthesis of performance TMPs/C composites still suffers from the coalescence and subsequent poor dispersion of NPs during pyrolysis, which can severely reduce the site density as well as activity of the as-prepared electrocatalysts. , Moreover, the naked TMPs dispersing on the C matrix are subject to poor durability under harsh electrochemical conditions, , for example, acidic/alkaline media at high voltages. Therefore, the development of a TMPs/C electrocatalyst with both high activity and durability for ZABs is of critical importance.…”
Section: Introductionmentioning
confidence: 99%
“…and single-atom catalysts (SACs). 13–16 Zhang et al . reported a single-atom Pt catalyst (Pt at –CoP MNSs/CFC), which exhibits outstanding performance with negligible onset potential, super high catalytic activity, and excellent durability that is even superior to Pt/C.…”
Section: Introductionmentioning
confidence: 99%
“…and single-atom catalysts (SACs). [13][14][15][16] Zhang et al reported a single-atom Pt catalyst (Pt at -CoP MNSs/CFC), which exhibits outstanding performance with negligible onset potential, super high catalytic activity, and excellent durability that is even superior to Pt/C. 17 Cheng et al report that subnanometer PtCo clusters with only 1.2% Pt loading (1.2%PtCo/ NPC) can achieve an extraordinary HER catalytic activity and durability with a mass activity of 13.83 A mg À1 at an overpotential of 20 mV, which is more than 65 times greater than that of the Pt/C catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Proton exchange membrane fuel cells (PEMFCs) are regarded as a clean and sustainable option to meet fossil fuel-free energy demands. 1,2 The main site for electrochemical reactions in fuel cells is the catalyst layer (CL), which contains catalysts and ionomers that conduct electrons and protons, respectively. 3 A typical CL consists of high-surface-area carbon powders promoting electron transfer, on which distributed metal catalysts such as Pt nanoparticles are used for accelerating the sluggish oxygen reduction reaction (ORR) in the PEMFC cathode.…”
mentioning
confidence: 99%